2010
DOI: 10.1007/s00701-010-0703-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and neuroprotective effects of alpha-lipoic acid on spinal cord ischemia–reperfusion injury in rabbits

Abstract: Although further studies considering different dose regimens and time intervals are required, the results of the present study prove that alpha-lipoic acid has favorable effects on experimental spinal cord ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 62 publications
3
19
1
Order By: Relevance
“…In addition, administration of alpha-lipoic acid significantly decreased these levels. Our study showed similar results with this study (17).…”
Section: █ Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, administration of alpha-lipoic acid significantly decreased these levels. Our study showed similar results with this study (17).…”
Section: █ Discussionsupporting
confidence: 83%
“…Corticosteroids, lazaroids, gangliosides, calcium channel blockers, free radical scavengers, magnesium, sodium channel blockers, cyclosporin A, opioid receptor antagonists, Nmethyl-D-aspartate (NMDA) receptor antagonists, and thyrotropin-releasing hormone have been shown to be effective in experimental SCI models. In-vivo and in-vitro neuroprotective effects of NMDA and non-NMDA receptor antagonists have been shown, however their clinical use is being limited by their major adverse effects (17).…”
Section: █ Discussionmentioning
confidence: 99%
“…Moreover, because of its amphiphilic nature, ALA readily penetrates all cells and tissues of the body, including the bloodbrain barrier (BBB). ALA also effectively increases the production of acetylcholine (neurotransmitter) and thereby maintains the integrity of the brain [12]. These findings strongly suggest a role for ALA in the treatment of various neurological disorders.…”
Section: Introductionmentioning
confidence: 77%
“…ALA administration, especially 100 vs. 50 mg, significantly reduced LPO levels to near normal. Emmez and coworkers [12] showed that ALA, with its freeradical scavenging activity, significantly suppressed LPO.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiologic mechanisms that underlie hypoxic/ischemic injury to the spinal cord have not been totally explained yet. [1][2][3][4][5][6][7] Thoracic and thoracoabdominal aortic intervention carries a significant risk of spinal cord ischemia, ranging from 5 to 20%. [8][9][10] Pouw et al 11 compared the neurological outcome between paraplegia caused by acute spinal cord ischemia syndrome and traumatic SCI, and found that neurological outcome was independent of the diagnosis.…”
Section: Introductionmentioning
confidence: 99%